Mathematical model of solving of a hydrodynamic problem in distributed computing environment - Глазок, О. М. (Problems of Informatization and Control, 2014)
The component elements of a mathematical model of the problem of assignment of calculation jobs to the nodes of a distributed computing system at mathematical modeling of liquid flow are considered. The use of this model allows to optimize the use of computing resources